Changes in the Near-Surface Air Temperature of the Northern Hemisphere during the Period of 1850–2014 - Yu.P. Perevedentsev; K.M. Shantalinskii (Учёные записки Казанского университета: Серия Естественные науки)
Changes in the near-surface air temperature of the Northern Hemisphere during the meteorological observations in 1850–2014 have been described. The periods of most pronounced temperature rising and falling, as well as 60–70-year-long fluctuations, have been revealed. It has been found that the recent decade (2005–2014) turns out to be the warmest for the entire time of reliable meteorological observations. The annual mean temperature anomaly averaged for the Northern Hemisphere peaked in 2005 (0.719 °C), 2010 (0.713 °C), and 2014 (0.750 °C). The analysis of the temperature series obtained at the Meteorological Observatory of Kazan University in 1828–2014 has shown that the mean annual air temperature increased by more than 4°С. About half of this change results from the effect of global factors. The significant growth of summer temperatures in Kazan during the early 21st century has been registered. At the same time, there is a tendency towards falling of the temperature from December to March and its significant rising in November.